N‐myc and STAT interactor correlates with severity and prognosis in acute‐on‐chronic liver failure of hepatitis B virus. Issue 10 (7th March 2019) - Xiong, Lifu; Du, Yanan; Zhou, Tianhui; Du, Bingying; Visalath, Phimphone; Lin, Lanyi; Bao, Shisan; Cai, Wei
Abstract: Background and Aim: Hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) is characterized by acute deterioration of chronic liver disease with excessive inflammation. N‐myc and STAT interactor (NMI), an inflammation‐mediated protein, involves in various inflammatory‐related diseases, but the role of NMI in development and prognosis in HBV‐ACLF remains to be elucidated. Methods: Serum NMI from healthy controls (HCs, n = 20), chronic hepatitis B (CHB, n = 50) patients, and HBV‐ACLF patients ( n = 50) was determined using ELISA. NMI from peripheral blood mononuclear cells and liver was confirmed using quantitative real‐time polymerase chain reaction, Western blot, and immunofluorescence. Results: Serum NMI was increased 1.9‐fold or 2.2‐fold from HBV‐ACLF patients compared with that from HCs ( P < 0.01) or CHB patients ( P < 0.01). Consistently, NMI from peripheral blood mononuclear cells was upregulated significantly from HBV‐ACLF patients compared with that from HCs and CHB patients at mRNA and protein levels. Hepatic NMI from HBV‐ACLF patients was 2.8‐fold higher than that from HCs. Serum NMI was correlated with Model for End‐stage Liver Disease, Chronic Liver Failure Consortium ACLF score, and ACLF grades. In contrast, serum NMI was significantly decreased in HBV‐ACLF ameliorated patients during follow‐up, whereas serum NMI was sustained at high levels in non‐ameliorated patients. Elevated serum NMI (≥ 198.5 pg/mL) was correlated with poor survival rate of HBV‐ACLF patients. Using receiver operating characteristics curves, it was suggested that serum NMI was a potential biomarker in predicting 3‐month mortality of HBV‐ACLF patients. Conclusions: Our study highlights the potential role of NMI in assessing the development and prognosis of HBV‐ACLF.